House Season 8 Disc 5 - Laurie, Hugh, 1959-; Universal Studios Home Entertainment (Firm) (Universal City, CA : Universal Studios Home Entertainment, 2012)
House is serving a prison sentence for driving his car into Cuddy's living room, and when his sentence ends early, he finds the Diagnostic Medicine Department has gone through a transition in his absence and he must deal with a new chain of command and personnel changes to his team.
Holding on -- Everybody dies.
Originally broadcast as single episodes of the 2011-2012 television program.
Special features on disc 5: House, M.D. swan song; The doctor directs: behind the scenes with Hugh Laurie; Everybody dies: a postmortem.
Hugh Laurie.
Not rated.
DVD, widescreen (1.78:1) presentation; Dolby digital 5.1 surround.
English dialogue; Spanish subtitles; subtitled for the deaf and hard of hearing.
Keywords: Physician and patient -- United States -- Drama; Hospitals -- Medical staff -- United States -- Drama; Hospital patients -- United States -- Drama; United States; Drama; Medical television programs; Television programs for the hearing impaired